Can read, will read four-pronged approach to the teaching of beginning reading - Padilla, Portia P.; Alfonso, Grace Javier 1950-.; University of the Philippines. Open University ([Quezon City] U.P. Open University, 2004)
Development of the four-pronged approach in teaching beginning reading, as Teacher Yvette Concepcion-Alcazar demonstrates this method upon her Kinder-Sampaguita class of the U.P. Integrated School (UPIS).
Executive producer: Maria Lurenda Suplido ; Associate producers: Mitzi Rivera and Judith Garcia ; Assistant director: Arminda V. Santiago ; Scriptwriter: Portia Padilla.
Keywords: Reading (Kindergarten).; Reading (Kindergarten) -- Language experience approach; Reading comprehension